Influence of CYP2C19 functional polymorphism on Helicobacter pylori eradication - Burhan ÖZDİL; Hikmet AKKIZ; Süleyman BAYRAM; Aynur BEKAR; Ersin AKGÖLLÜ; Macit SANDIKÇI (Turkish Journal of Gastroenterology, 2019)
-